Esencia e identidad en filosofía de la taxonomía (Culturas Científicas, 2018)
If we analyze those 'phylogenetic definitions' of taxa to which alludes the relational neo-essentialism that today is often opposed to taxonomic individualism, we will see that they function as designations of individual entities. On the other hand, if we scrutinize more closely what it is that so called 'relational essence' which would be given by the individual common origin of each taxon, we will see that would be better understanding it as the individualizing principle, or haecceitas, of a particular entity rather than as the defining essence, or quiditas, of a natural class. This is not a too much crucial argument in favor of taxonomic individualism; but it may show that relational neo-essentialism does not bring anything too significant to the discussion concerning the ontological status of taxa.